The thief [large type] : an Isaac Bell adventure - Cussler, Clive (Cussler, Clive. Isaac Bell novels., 2012)
When a scientist he recently rescued from kidnappers is murdered, private investigator Isaac Bell discovers that a ruthless agent wants the scientist's secret new invention in order to exploit it to seize power for Germany.